Spatial data for slum upgrading: Volunteered Geographic Information and the role of citizen science - Hachmann, Samyra; Jokar Arsanjani, Jamal; Vaz, Eric de Noronha (Habitat international, 2018)
Urban informal settlements are growing rapidly, placing slum upgrading on the political agenda worldwide. This paper presents a survey on existing approaches integrating spatial data and slum upgrading. More precisely, it aims to explore the possibility of exploiting Volunteered Geographic Information (VGI) and Citizen Science (CS) as potential practices for gathering spatial information about informal settlements. Challenges include an asymmetric access to technology and GIS skills, as well as the recognition and validation of citizen data. Opportunities, on the other hand, include the possibility for citizens to express their needs to municipalities and the provision of up-to-date, accurate information to urban planners. Due to its bottom-up conceptualization of data collection, VGI could take a leading role in providing spatial information to planning efforts which aim at understanding and improving the realities of informal settlements.